Mechanical pruning and soil organic amendments in vineyards of Syrah: effects on grape composition - Botelho, Manuel (2021)
Aim: The interaction of mechanized pruning systems and soil organic amendment can increase vine productivity. However, since the increase in p roductivity may affect grape composition, this study aimed to understand the effects of the interaction between these two practices. Methods and materials: Two field trials were implemented in Shiraz vineyards in two different wine regions. Mechanical hedge pruning was compared with hand spur pruning and four different organic amendments were tested: biochar, municipal solid waste compost, cattle manure and sewage sludge. Results: Mechanical pruning reduced the total soluble solids (TSS) and pH of the grapes, but had no effects on the other variables. Organic amendments also reduced TSS, especially sewage sludge, and tended to reduce total anthocyanins and total phenols. The effect of the interaction between both factors on grape composition was never significant. A negative relationship between yield and TSS was observed, while titratable acidity had no relationship with yield. Total anthocyanins were also negatively related to yield. A positive relation between TSS and total anthocyanins was also observed. Conclusions: The results show that the combination of mechanical pruning and soil organic amendment is a powerful tool for increasing productivity, but it has some effects on grape composition. Significance and impact of study: The reduction in some fruit composition variables showed that, while mechanical pruning does not significantly affect grape composition, the choice of type and amount of organic amendment will depend on the destination of the grapes